1988
DOI: 10.1007/bf01794689
|View full text |Cite
|
Sign up to set email alerts
|

A sphenoorbital encephalocele — clinical, radiological, and morphological findings

Abstract: We report here on congenital sphenoorbital encephalocele which could not be disclosed by computed tomography including contrast medium application or by orbital sonography. Surgery and histological examination were necessary to establish correct the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The surgical defects of the orbital roof (frontal bone) and posterior wall (sphenoid bone) should be reconstructed. Bornemann et al [19] reported a case of spheno-orbital encephalocele which was operated by the transfrontal orbitotomy, they could only achieve partial removal of the cyst. Bornemann et al [19] reported a case of spheno-orbital encephalocele which was operated by the transfrontal orbitotomy, they could only achieve partial removal of the cyst.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical defects of the orbital roof (frontal bone) and posterior wall (sphenoid bone) should be reconstructed. Bornemann et al [19] reported a case of spheno-orbital encephalocele which was operated by the transfrontal orbitotomy, they could only achieve partial removal of the cyst. Bornemann et al [19] reported a case of spheno-orbital encephalocele which was operated by the transfrontal orbitotomy, they could only achieve partial removal of the cyst.…”
Section: Discussionmentioning
confidence: 99%